2018
DOI: 10.1038/s41598-018-33151-1
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Repair Protein OGG1 Protects Against Obesity by Altering Mitochondrial Energetics in White Adipose Tissue

Abstract: Obesity and related metabolic pathologies represent a significant public health concern. Obesity is associated with increased oxidative stress that damages genomic and mitochondrial DNA. Oxidatively-induced lesions in both DNA pools are repaired via the base-excision repair pathway, initiated by DNA glycosylases such as 8-oxoguanine DNA glycosylase (OGG1). Global deletion of OGG1 and common OGG1 polymorphisms render mice and humans susceptible to metabolic disease. However, the relative contribution of mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 68 publications
(60 reference statements)
8
64
0
Order By: Relevance
“…Fecal samples were collected after 6 weeks of feeding. As with previous cohorts [26,60], Ogg1 -/mice gained more weight ( Fig 1A) and more fat mass ( Fig 1B) upon HFD-administration, relative to WT controls.…”
Section: Increased Body Weight and Adiposity In Ogg1 -/Mice Fed A Hfdsupporting
confidence: 87%
“…Fecal samples were collected after 6 weeks of feeding. As with previous cohorts [26,60], Ogg1 -/mice gained more weight ( Fig 1A) and more fat mass ( Fig 1B) upon HFD-administration, relative to WT controls.…”
Section: Increased Body Weight and Adiposity In Ogg1 -/Mice Fed A Hfdsupporting
confidence: 87%
“…OGG1 has two isoforms: nuclear and mitochondrial (11). Multiple approaches have demonstrated that mitochondrial OGG1 is crucial for maintenance cell survival, mitochondrial function, and energetics (26,27). Recognition and repair of 8-OH-dG lesions is carried out by the mitochondrial isoform, and we previously showed that Ogg1 −/− BMDMs were more sensitive to menadione-induced mtDNA oxidative damage, and that inflammation caused by oxidized DNA damage and dyslipidemia-induced metabolic stress resulted in accelerated atherosclerosis in Ogg1 −/− Ldlr −/− mice (22).…”
Section: Discussionmentioning
confidence: 99%
“…BER removes small non-helix distorting lesions such as oxidized and deaminated bases, alkylation damage, and single-strand breaks [112,113,114]. The importance of this pathway for the maintenance of mtDNA integrity is evidenced by the numerous pathological phenotypes described in human cohorts and animal models with defects in BER [81,82,115,116,117,118,119].…”
Section: Induction Of Mitochondrial Dna Damagementioning
confidence: 99%